Achieving sustainability through financial literacy training. (3rd February 2022) - Narula, Swati
Minimal is known about the impact of financial literacy training on improved financial outcomes. This is due to scanty research being carried out in this regard which may be due to the reason that evaluating the impact of financial education is a daunting task. However, the few studies that have been conducted in different parts of the world indicate that financial literacy programmes can make a difference. The present study is thus an attempt to gauge the level of financial literacy of retail investors in Delhi and to identify whether there is any considerable difference in financial literacy scores of those who attended financial literacy/awareness training/programme and those who did not attend any financial literacy/awareness training/programme. The statistical analysis made through Cramer's V and student's t-test reveals that the mean financial literacy score of ones who have attended financial literacy programmes is significantly different from those who did not.